RETRACTED: Reconstruction of Vitamin C Test Worksheet for Junior High School Class VIII with ANCOR Stages - Resti, Novita; Supriatno, Bambang; Amprasto, Amprasto (UNIVERSITAS ISLAM NEGERI RADEN INTAN LAMPUNG, 2024)
Practicum is one of the learning methods that can help students construct various psychomotor skills, higher order thinking, and characterise learning outcomes. However, currently there are still many worksheets that do not meet the standards and do not show knowledge construction. In addition, there has been no research on the reconstruction of the vitamin c test worksheet. Therefore, it is necessary to analyse and reconstruct the vitamin c test worksheet. The method used is descriptive qualitative with the ANCOR (Analyze, Trial and Reconstruct) stage. The population in this study was vitamin c test worksheets for junior high school class VIII used by teachers. The sample in this study was one of the worksheets used in learning at school, circulating on the internet and having incomplete components. The sampling technique was purposive sampling. The results of the analysis obtained that the worksheet does not comply with the standards, so it is necessary to reconstruct the worksheet. The reconstruction of this worksheet can be an alternative worksheet to overcome the shortcomings of the current worksheet.ABSTRAK: Praktikum merupakan salah satu metode pembelajaran yang dapat membantu mahasiswa membangun berbagai keterampilan psikomotorik, pemikiran tingkat tinggi, dan mengkarakterisasi hasil belajar.Namun, saat ini masih banyak lembar kerja yang tidak memenuhi standar dan tidak menunjukkan konstruksi pengetahuan. Selain itu, belum ada penelitian tentang rekonstruksi lembar kerja tes vitamin c. Oleh karena itu, perlu untuk menganalisis dan merekonstruksi lembar kerja tes vitamin c. Metode yang digunakan adalah kualitatif deskriptif dengan tahap ANCOR (Analyze, Trial and Reconstruct). Populasi dalam penelitian ini adalah lembar kerja tes vitamin c untuk SMP kelas VIII yang digunakan oleh guru. Sampel dalam penelitian ini merupakan salah satu lembar kerja yang digunakan dalam pembelajaran di sekolah, beredar di internet dan memiliki komponen yang tidak lengkap. Teknik pengambilan sampel adalah purposive sampling. Hasil analisis diperoleh bahwa lembar kerja tidak sesuai dengan standar, sehingga perlu dilakukan rekonstruksi lembar kerja. Rekonstruksi lembar kerja ini dapat menjadi alternatif lembar kerja untuk mengatasi kekurangan lembar kerja saat ini.